How (sub)morphological relicts of perceptual parameters still influence the synchronic use & even might had an impact on the United States presidential election (Signifiances (Signifying), 2017)
This contribution focuses on the close link between sensorimotor actions and language. The interaction between perceptual and conceptual parameters will be illustrated in detail and from different perspectives via specific examples. Furthermore, the analysis will extend beyond morphological evidence to include the role of sub morphological relicts of perceptual and conceptual parameters. It will also raise the question of whether submorphemic knowledge might have had an impact on the United States presidential election and helped Donald Trump to become the 45th President of the United States. In short, this paper seeks to tackle three questions: first, how aware are we that words are never „innocent“, second, how transparent are words, and finally, is it possible to sketch semantic mappings from the initial encoding strategies on to the synchronic „power“ of a given word.Perceptual Parameters, Conceptual parameters, Concepts, Source domain, SubmorphemesLa présente contribution traite du lien étroit entre les actions sensorimétriques et notre langue. L’interaction entre les paramètres perceptuels et conceptuels sera illustrée en détail et à l’aide d’exemples spécifiques à travers différentes perspectives. L’analyse ne s’arrêtera pas aux éléments morphologiques des paramètres susdits ; elle traitera également leurs aspects phonétiques et posera la question de savoir si les connaissances submorphologiques ont pu avoir un impact sur les résultats de l’élection du 45ème président des Etats-Unis. Dans cet article, il s’agira également de trouver des réponses à trois autres questions: premièrement, est-on conscient du fait que les mots ne sont jamais innocents ? Deuxièmement, quel est le degré de transparence synchronique d’un mot ? Et finalement, est-il possible d’illustrer les réseaux sémantique et conceptuel à partir des domaines sources et jusqu’aux domaines cibles pour montrer le "pouvoir" d’un mot.Paramètres perceptuels,  Paramètres conceptuels, Concepts, Domain Source, Submorphèmes